Urinary Peptides Significantly Associate with COVID‐19 Severity: Pilot Proof‐of‐Principle Data and Design of a Multicentric Diagnostic Study. Issue 24 (8th October 2020) - Wendt, Ralph; Kalbitz, Sven; Lübbert, Christoph; Kellner, Nils; Macholz, Martin; Schroth, Stefanie; Ermisch, Jörg; Latosisnka, Agnieszka; Arnold, Benjamin; Mischak, Harald; Hartmut Beige, Joachim; Metzger, Jochen
Abstract: SARS‐CoV‐2 infection results in a mild‐to‐moderate disease course in most patients, allowing outpatient self‐care and quarantine. However, in ≈10% of cases a two‐ or three‐phasic critical disease course with starting from day 7 to 10 is observed. To facilitate and plan outpatient care, biomarkers prognosing such worsening at an early stage appear of outmost importance. In this accelerated article, the identification of urinary peptides significantly associated with SARS‐CoV‐2 infection, and the development of a multi‐marker urinary peptide based test, COVID20, that may enable prognosis of critical and fatal outcomes in COVID‐19 patients is reported. COVID20 is composed of 20 endogenous peptides mainly derived from various collagen chains that enable differentiating moderate or severe disease from critical state or death with 83% sensitivity at 100% specificity. Based on the performance in this pilot study, testing in a prospective study on 1000 patients has been initiated.